TPACK-Based ICT Integration to Promote Joyful Learning in EFL Classrooms under the Indonesia Merdeka Curriculum - Nathasya Jasmine Salsabila; Alfan Zuhairi (Al-Qalam Institute, 2025)
This study investigates English as a Foreign Language (EFL) teachers’ perceptions of TPACK-based ICT integration in promoting joyful learning within the implementation of the Merdeka Curriculum in Indonesia. Using a qualitative descriptive design, data were collected through semi-structured interviews with an English teacher at a private school who had participated in a Deep Learning workshop. The study explored how teachers integrated technological, pedagogical, and content knowledge (TPACK) to create meaningful and engaging classroom experiences. The findings revealed that ICT-based media, such as PowerPoint presentations and interactive learning applications, effectively increased students’ attention, motivation, and classroom interaction. Teachers also employed pedagogical strategies, including project-based learning, group discussions, and educational games, to support joyful and student-centered learning. In addition, the study found that teachers’ TPACK competencies developed through training and reflective practice, particularly in the areas of Technological Knowledge, Pedagogical Knowledge, and Content Knowledge. Despite limited school facilities, teachers demonstrated adaptability and creativity in designing contextual and interactive English learning activities. The study concludes that TPACK-based ICT integration effectively supports the implementation of joyful learning and highlights the importance of continuous professional development in strengthening teachers’ competencies in technology-enhanced EFL instruction under the Merdeka Curriculum.